Southeastern Europe: Intelligence and Security Services Battlefield? - Akrap, Gordan (2013)
In this presentation authors presented process of democratization and establishing an intelligence and security system in Croatia after the elections in 1990. They show the case of Croatia in which small inteligence service can become reliable partner for international community in a process of solving major international problems.